Reduced Serum Butyrylcholinesterase Activity Indicates Severe Systemic Inflammation in Critically Ill Patients. (11th February 2015) - Zivkovic, Aleksandar R.; Schmidt, Karsten; Sigl, Annette; Decker, Sebastian O.; Brenner, Thorsten; Hofer, Stefan
Abstract : Systemic inflammation is an immune response to a nonspecific insult of either infectious or noninfectious origin and remains a challenge in the intensive care units with high mortality rate. Cholinergic neurotransmission plays an important role in the regulation of the immune response during inflammation. We hypothesized that the activity of butyrylcholinesterase (BChE) might serve as a marker to identify and prognose systemic inflammation. By using a point-of-care-testing (POCT) approach we measured BChE activity in patients with severe systemic inflammation and healthy volunteers. We observed a decreased BChE activity in patients with systemic inflammation, as compared to that of healthy individuals. Furthermore, BChE activity showed an inverse correlation with the severity of the disease. Although hepatic function has previously been found essential for BChE production, we show here that the reduced BChE activity associated with systemic inflammation occurs independently of and is thus not caused by any deficit in liver function in these patients. A POCT approach, used to assess butyrylcholinesterase activity, might further improve the therapy of the critically ill patients by minimizing time delays between the clinical assessment and treatment of the inflammatory process. Hence, assessing butyrylcholinesterase activity might help in early detection of inflammation.